PAHAM KETUHANAN MORI KRAENG DALAM TOROK TUDAK PENTI DI KAMPUNG TENDA KABUPATEN MANGGARAI - Yosef Gunawan; Marianus Aventino Penabur; Aquilio Jeane Windy Putra (Bahasa Indonesia, 2026)
Torok Tudak Penti is a form of traditional prayer that holds a central position in the Penti ceremony, an annual thanksgiving rite performed by the Manggarai people to honor Mori Kraeng (God) and the ancestors (wura agu ceki). As the culmination of the entire ritual process, Tudak Penti not only marks the conclusion of the ceremony but also serves as a profound spiritual and cultural moment. In this procession, the Torok is recited in a distinct and sacred Manggarai language, following a fixed structure consisting of three main parts: respectful greetings to God and the ancestors, praise expressing acknowledgment of their greatness and goodness, and petitions for blessings such as bountiful harvests, protection, health, and communal well-being. The Torok in Tudak Penti reflects the hierarchical relationship between humans, God, and the ancestors, emphasizing the community’s absolute dependence on Mori Kraeng as the ultimate source of life. This prayer is not merely a verbal expression but also serves as a spiritual vehicle that reinforces cultural, moral, and religious values in daily life. As a collective and sacred spiritual expression, Torok Tudak Penti unites two essential dimensions of Manggarai life: the vertical dimension, which connects humans with the divine and the ancestors, and the horizontal dimension, which underscores the importance of relationships within the community. Thus, Torok Tudak Penti not only reveals the richness of local tradition but also offers a profound understanding of the concept of divinity in Manggarai culture which is holistic, contextual, and transcendent in nature.